Neuropsychiatric Systemic Lupus Erythematosus and Posterior Reversible Encephalopathy Syndrome in a Young Woman: A Case Report - Mohammed Bawazir, Yasser; Wasim Anshasi, Neda´a (Current Rheumatology Reviews, 2023)
Introduction: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease with variable clinical presentation, including neuropsychiatric manifestations. It has a different diagnostic approach and several different therapeutic options. Case Report: We describe a case of a young woman who first presented with arthritis, serositis, and pancreatitis, and was treated with mycophenolate mofetil initially. The patient presented with neurological symptoms suggestive of neuropsychiatric manifestations three weeks later, confirmed by Brain Magnetic Resonance Imaging (MRI). The treatment was changed to cyclophosphamide; however, the day after the infusion, she developed status epilepticus and was admitted to the intensive care unit. Repeated brain MRI revealed Posterior Reversible Encephalopathy Syndrome (PRES). Cyclophosphamide was discontinued and rituximab was initiated. The patient’s neurological manifestations improved, and she was discharged after 25 days of use. Conclusion: Immunosuppressive agents, such as cyclophosphamide have been described as a potential risk factor for PRES; however, it is not clear from the available literature whether cyclophosphamide therapy is just a marker of more severe SLE or a true risk factor for PRES.
Keywords: SLE